Business cycle correlation between the Euro area and the Balkan countries - Sofia Gouveia (International Journal of Economic Sciences and Applied Research, 2014)
This paper examines the degree of trade integration and business cycle synchronisation between eight Balkan countries and the Euro area over the period 2000:1-2011:4. The main findings are that Slovenia and the Former Yugoslav Republic of Macedonia exhibit a high level of openness relative to Euro area and seem to have achieved a large degree of business cycle synchronisation with the aggregate Euro area cycle. The other Balkan countries are characterized by high trade integration with the EMU (except Greece and Turkey) and a rather modest degree of association with the Euro area cycle, although Turkey is nearest the average of the EMU countries. We further document that there is a tendency for an increase in the degree of synchronisation with EMU for all Balkan countries. We also note, however, that at the end of the period, the degree of synchronisation has become less pronounced.
Keywords: E32; F15; F41; 330; Business cycles; Synchronization; Balkan countries; European integration; Euro area